A Comparison of Thromboelastography with Heparinase or Protamine Sulfate Added In Vitro during Heparinized Cardiopulmonary Bypass - Spiess, Bruce D; Wall, Michael H; Gillies, Bruce S; Fitch, Jane C K; Soltow, Louise O; Chandler, Wayne L (Thrombosis and Haemostasis, 1997)
Thromboelastography (TEG) has been used after cardiopulmonary bypass (CPB) to diagnose excessive postoperative hemorrhage. Conventional TEG during CPB is not possible due to the sensitivity of the TEG to even small amounts of heparin, which produces a nondiagnostic tracing. The purpose of this study was to compare heparin neutralization using heparinase or protamine in TEG blood samples obtained during CPB. TEG testing was performed on 48 patients before, during and after CPB. Tissue plasminogen activator activity and antigen were measured on a subset of 32 patients. We found: 1) heparinase neutralized at least 10 IU/ml heparin while 1.6 ug/ml protamine neutralized up to 7 IU/ml heparin, 2) in samples with complete heparin neutralization by both methods, there was no significant difference in the R values, 3) while there was good correlation for other TEG parameters between heparinase and protamine treated samples, heparinase treatment produced shorter K values and higher angle, MA and A60, 4) while fibrinolysis was detected using both methods, heparinase treatment suppressed fibrinolysis in the TEG in both samples from patients and after in vitro addition of tissue plasminogen activator, 5) TEG was not a sensitive indicator of t-PA activity, detecting only 21% of samples with increased t-PA activity during bypass, and 5) heparinase was at least 100 times more expensive than protamine. We conclude that while both heparinase and protamine can be used to neutralize heparin in TEG samples obtained during CPB, protamine neutralization is more sensitive to fibrinolysis and less expensive, but the protamine dose must be carefully selected to match the heparin level used at individual institutions.